Efek Pengaplikasian Sitokinin Dan Paclobutrazol Terhadap Ukuran Rimpang Tanaman Kunyit (Curcuma Domestica Val.) - Fitriyah, Nur; Helilusiatiningsih, Nunuk; Adji, Galih (JURNAL ILMIAH AGRINECA, 2024)
Since COVID-19, the demand for turmeric has continued to increase both domestically and for export opportunities. This encourages the continued development of turmeric cultivation. The use of growth regulators can be done to regulate plant growth patterns. This study aims to determine the effect of the application of cytokinin and paclobutrazole on the size of the rhizomes of turmeric plants (Curcuma domestica Val.). This study used a Randomized Group Design (RAK) with 2 treatment factors, which are : Factor I Cytokinin (S) consists of 3 kinds, namely S1: 0 mg/l water, S2: 10 mg/l water and S3: 20 mg/l water while, Factor II: Paclobutrazole (K) consists of 4 kinds, namely: P1: 0 g/l water, P2: 0.50 g/l water, P3: 0.75 g/l water, P4: 1 g/l water. Based on the results of the experiment, it shows that the application of ZPT Cytokinin (BAP) and Paclobutrazole on turmeric plants gives a real interaction effect on the observation of vegetative growth of plant height, while on the harvest observation variable only gives a real interaction effect on the observation of plant biomass and not real on the number of tubers and tuber weight. The concentration and time of application of cytokinin (BAP) and paclobutrazole will affect the nature of stimulation and inhibition of growth, the application of BAP at a concentration of 10-20 mg / l water can increase growth but if combined with paclobutrazole above 0.75 g / l water will actually have an inhibiting effect.